2010
DOI: 10.1007/s10886-010-9839-6
|View full text |Cite
|
Sign up to set email alerts
|

Attractants for Rice Leaf Bug, Trigonotylus caelestialium (Kirkaldy), are Emitted from Flowering Rice Panicles

Abstract: Volatiles were extracted from rice plants of various growth stages with solid-phase microextraction (SPME) and analyzed by gas chromatography-mass spectrometry (GC-MS) to identify attractants that cause invasion of the rice leaf bug Trigonotylus caelestialium (Kirkaldy) into paddy fields. The composition of volatile blends produced by rice plants changed with rice development. In addition, volatile blend compositions differed between the panicles and the stems and leaves. The relative geranyl acetone content w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
45
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(47 citation statements)
references
References 29 publications
2
45
0
Order By: Relevance
“…This result was similar to that reported in Cheng et al [30]. Fujii et al revealed that during the flowering stage, rice panicles released (E)-b-caryophyllene [31]. We detected GUS activity in glumes but not stamens, implying that glumes might be the main organ for producing (E)-bcaryophyllene.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This result was similar to that reported in Cheng et al [30]. Fujii et al revealed that during the flowering stage, rice panicles released (E)-b-caryophyllene [31]. We detected GUS activity in glumes but not stamens, implying that glumes might be the main organ for producing (E)-bcaryophyllene.…”
Section: Discussionsupporting
confidence: 92%
“…Using transformed rice plants overexpressing an (E)-b-caryophyllene synthase gene, OsCAS (namely OsTPS3), Cheng et al showed that (E)-b-caryophyllene attracts Anagrus nilaparvatae [30], an egg parasitoid of rice planthoppers. Moreover, Fujii et al found that (E)-b-caryophyllene emitted from flowering rice panicles attracts the rice leaf bug Trigonotylus caelestialium [31]. Recently, our study revealed that the constitutively produced (E)-b-caryophyllene in rice is attractive to BPH as well as to its parasitoids and predators [25].…”
Section: Introductionmentioning
confidence: 59%
See 1 more Smart Citation
“…Behavioural response to plant volatiles have also been reported in mirid species (e.g. Fujii et al 2010), including the North American Lygus species as well (Blackmer et al 2004;Whitbey 1999). Also, for the European tarnished plant bug, it was shown in olfactometer and wind tunnel experiments, that host plant volatiles provided an important stimulus for the species (Frati et al 2008).…”
Section: Introductionmentioning
confidence: 87%
“…Both rice bug species are attracted by odors released from host plants [10]- [12] [19]. Attraction behavior is altered by olfactory learning in several phytophagous insects [20]- [24].…”
Section: Discussionmentioning
confidence: 99%